Academic publishing in disaster risk reduction: past, present, and future. Issue 1 (20th March 2020) - Alexander, David; Gaillard, JC; Kelman, Ilan; Marincioni, Fausto; Penning‐Rowsell, Edmund; van Niekerk, Dewald; Vinnell, Lauren J.
Abstract : Nowadays there are approximately 80 Anglophone journals that deal primarily with disaster risk reduction (DRR) and allied fields. This large array signals a sustained, if uneven, growth in DRR scholarship but also competition between the offerings of different publishers and institutions. The purpose of this article is first to summarise the development of academic publishing on DRR from its early beginnings to the present day. The paper then evaluates the current state of publishing in this field and discusses possible future trends. Next, it identifies some possible opportunities, challenges, expectations, and commitments for journal editors both within DRR and academia more broadly, including those that refer to changes in the use of terminology, the relentless increase in the number of papers submitted, the expansion and dangers of predatory journals, different peer review models, open access versus paywalls, citations and bibliography metrics, academic social networks, and copyright and distribution issues.